Pengaruh Media Pembelajaran Interaktif Block Letters Terhadap Kemampuan Pengenalan Huruf Pada Anak Usia 4-5 Tahun - Mutiara, Mutiara; Siti Nurhidayah Ilyas; Sri Wahyuni Asti; Nurul Jamiah Sidiq (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2025)
This research aimed to investigate the impact of interactive learning media using block letters on the letter recognition skills of children aged 4–5 years at TK Aisyiyah Bontosunggu. A quantitative approach was utilized, adopting a quasi-experimental design with a non-equivalent control group structure. The study involved 16 children, divided evenly into an experimental group and a control group. Data were gathered through observation, pre-test and post-test evaluations, and documentation. The experimental group was taught using block letter media, while the control group used alphabet posters. Results demonstrated a notable enhancement in letter recognition among children exposed to block letter media. Improvements were observed in their ability to recognize letter sounds, identify letter shapes, and find letters within words. Statistical analysis using the Wilcoxon Signed Rank Test yielded a significance level (2-tailed) of less than 0.05, confirming the positive effect of block letter media on letter recognition in young children. The study suggests incorporating interactive, play-based learning tools to support early literacy development.